A recombinant field strain of Marek's disease (MD) virus with reticuloendotheliosis virus long terminal repeat insert lacking the meq gene as a vaccine against MD. Issue 5 (29th January 2015) - Su, Shuai; Cui, Ning; Zhou, Yu; Chen, Zimeng; Li, Yanpeng; Ding, Jiabo; Wang, Yixin; Duan, Luntao; Cui, Zhizhong
Abstract Marek's disease virus (MDV) GX0101, which is a field strain with a naturally occurring insertion of the reticuloendotheliosis virus (REV) long terminal repeat (LTR) fragment, shows distinct biological activities. Deletion of the meq gene in GX0101 contributes to its complete loss of pathogenicity and oncogenicity in SPF chickens, but this virus has a kanamycin resistance gene (kanr) residual at the site of meq gene. In the present study, the kanr was knocked out and a meq-null virus with a good replicative ability termed SC9-1 was selected. In vivo studies showed that SC9-1 had no pathogenicity or tumorigenicity to chickens. There were no obvious impacts on chicken weight, immune organ index or antibody levels induced by avian influenza virus (AIV)/newcastle disease virus (NDV) inactivated vaccines compared with the control group. The SC9-1 virus provided superior protection than CVI988/Rispens vaccine in both SPF chickens and Hy-line brown chickens when challenged with a very virulent MDV (rMd5 strain). There was no obvious change in SC9-1 protection against MDV rMd5 in SPF chickens after 20 passages in chicken embryonic fibroblast cells (CEFs). In conclusion, SC9-1 is a safe and effective vaccine candidate for the prevention of Marek's disease.